A practical approach of salt and protein restriction for CKD patients in Japan. Issue 1 (December 2016) - Iseki, Kunitoshi; Yamagata, Kunihiro
Abstract Dietary management, in particular salt and protein restriction is fundamental for the proper care of CKD patients. Therefore, a practical guide to the dietary treatment may be helpful among progressive CKD patients. In Japan, two academic societies such as Japanese Society of Nephrology and Japanese Society for Dialysis Therapy have recently published Guidelines for Dietary Management for non-dialysis dependent CKD and dialysis-dependent CKD, respectively. In this manuscript, we summarized the practical guide for salt and protein restriction from the Japanese Society of Nephrology to retard the progression of CKD to endstage renal disease. This guide will promote further the collaboration of Nephrologists and Dietitians.